Supporting English Graduates Transition to Work: A Sustainable Careers Ecosystem Approach - Lennox, Emma (GILE Journal of Skills Development, 2025)
In an era of accelerating automation, human-centered skills such as critical thinking, communication, and adaptability - hallmarks of an English degree - are becoming increasingly vital in the workplace. And yet English degree enrolment numbers, and value perception in a capitalist society, are both decreasing. This study examines experiences of English graduates, as they transition from a higher education non-specialised degree to the workplace. It uses the Sustainable Careers Ecosystem Theory (SCET) to highlight challenges faced, relevance of acquired skills, and support needed during this transitional period. Employing a constructivist grounded theory approach, the research uses qualitative semi-structured interviews with 21 English graduates. Data was thematically analysed and three core themes constructed: (1) who is responsible for English graduate employability, highlighting key stakeholders including universities, careers services, future employers, and individual students; (2) the importance of identifying a next step and embracing flexibility rather than pursuing a narrow predefined career goal; and (3) the retrospective appreciation of skills acquired through studying English. This research addresses a gap in the literature by examining the experiences of non-specialist course alumni, focusing on the sustainability of English studies and the relevance of academic skills to the current labour market. It expands the use of the SCET to non-specialist subjects, highlighting its application in diverse sectors. Findings highlight the need for enhanced collaboration between universities, careers services, and employers to support English graduates' transition into the workplace, addressing options available and articulation of skillset. This research contributes to ongoing discourse on non-specialist degree value in contemporary job markets, influencing educational policy and career guidance practices, highlighting the importance of the SCET.